Examining family and community nurses' core competencies in continuing education programs offered in primary health care settings: An integrative literature review. (February 2023) - Azimirad, Mina; Paloniitty, Riina; Papathanasiou, Ioanna V.; Aleo, Giuseppe; Catania, Gianluca; Pozzi, Francesca; Bagnasco, Annamaria; Turunen, Hannele
Abstract: Aim: To identify gaps in existing family and community nurse (FCN) continuing education programs and to investigate whether FCN core competencies are covered in continuing education programs offered in primary health care settings. Background: In global pandemics such as COVID-19, there is an urgent need for staff development using transformative learning and help registered nurses build up their competencies and form a new professional identity as family and community nurses (FCNs). Therefore, FCN education programs become of high importance to enhance nurses' core competencies through continuing education. Methods: An integrative review of the literature was conducted applying the Whittemore and Knafl methodological strategy for studies published between 2015– June 2021. Results: FCN core competencies, including the "decision-making process, navigation as care coordinator and patient advocate and promoting individual and family health to support the quality of nursing care, " were poorly covered in the FCN programs. Specifically, e-health played a very limited role in FCN continuing education, while ethics, managing change, managing disparity and diversity and leadership skills, did not emerge at all. Conclusion: The identified gaps can be incorporated into future FCN continuing education programs and may help improve nurses' competence and health care delivery and support new integrated models of care, namely, person-centered and community-based models.